Static magnetic field regulates proliferation, migration, differentiation, and YAP/TAZ activation of human dental pulp stem cells. (2nd September 2018) - Zheng, Lisha; Zhang, Lingyu; Chen, Luoping; Jiang, Jingyi; Zhou, Xiaocheng; Wang, Ming; Fan, Yubo
Abstract: The dental pulp stem cells (DPSCs) are a population of mesenchymal stem cells, which have multilineage potential and high proliferation. DPSCs are regarded as a promising tool for tissue regeneration of dentine, dental pulp, bone, cartilage, and muscle. Recently, magnetic materials have become commonly applied in dental clinics. Static magnetic field has been reported to regulate the proliferation, migration, or differentiation of stem cells. However, whether static magnetic fields affect DPSCs is still unknown. In our study, we investigated the effect of static magnetic field on the proliferation, migration, and differentiation of DPSCs. The results indicated that static magnetic field rearranged the cytoskeleton of DPSCs. A static magnetic field of 1 mT increased DPSC proliferation, as well as the gene expression of several growth factors such as FGF‐2, TGF‐β, and VEGF. Moreover, the static magnetic field promoted the migration of DPSCs by regulating MMP‐1 and MMP‐2 gene expression. Static magnetic field of 1 mT also induced osteo/odontogenesis and mineralization in DPSCs. Otherwise, the static magnetic field recruited YAP/TAZ to the nucleus, inhibited the phosphorylation of YAP/TAZ, and upregulated the two YAP/TAZ‐regulated genes, CTGF and ANKRD1. Cytoskeleton inhibitor, cytochalasin D, obviously inhibited the nuclear localization of YAP/TAZ. When YAP/TAZ were knocked‐down, the static magnetic field‐induced mineralization of DPSCs was diminished. Our findings provide an insight into the effect of static magnetic field on DPSCs and provide the foundation for the future tissue regeneration.